Feasibility of low-field magnetic resonance imaging (lf-MRI) for longitudinally evaluating experimentally induced lumbar intervertebral disc injuries in goat models (Capra hircus): A pilot study - Jeryl C. Jones; Mario J. Krussig; Matthew W. Breed; Cerano D. Harrison; John W. Gilpin; Guillermo M. Rimoldi; Jeremy J. Mercuri; Ahmed A. B. Ali; William C. Bridges (PLoS ONE, 2026)
Intervertebral disc injury and degeneration are among the most common causes of lower back pain and debilitation in humans. This prospective, descriptive, pilot study was designed to support our team’s long-term research goals of measuring effects of novel therapies for lumbar disc injury and degeneration using small ruminant translational research models. Our overall aim was to determine whether low-field magnetic resonance imaging (lf-MRI) would be a feasible technique for longitudinally assessing surgical microdiscectomy-induced lumbar disc injury and degeneration in goat models ( Capra hircus ). Four, female, skeletally mature, Nubian-breed goats were used. One goat was used to refine and standardize imaging and surgical protocols and the remaining three were scanned one week before and 3, 6, and 12 weeks after surgery in which two discs were injured via microdiscectomy. Gross pathologic and histologic assessments for all discs were performed at the 12-week time point. We introduced a standardized lf-MRI image acquisition protocol that required 30–60 minutes (median 47.5 minutes) and yielded good quality images. We also introduced standardized protocols for quantifying disc height index (DHI) and MRI index values from lf-MRI images. All animals tolerated anesthesia well with no signs of distress. Two of the 3 goats studied longitudinally developed unexpected, non-infectious discospondylitis at the operated disc locations. The lf-MRI characteristics of non-infectious discospondylitis in goats have not been previously reported. These findings can be used as background for future studies evaluating the feasibility of using lf-MRI as a technique for longitudinally measuring IVD injury and degeneration in goat models.